Robowealth: Bringing investment opportunities to the masses - CHIYACHANTANA, Chiraphol N. (Institutional Knowledge at Singapore Management University, 2022)
Chonladet Khemarattana, CEO of Robowealth Group, an investment advisory company, wanted to disrupt the traditional investment advisory industry in Thailand by promoting greater financial inclusion. He founded a financial technology (FinTech) start-up, Robowealth, that could provide investment opportunities for every Thai citizen; it would help Thais achieve financial freedom. The traditional investment advisory industry helped high net worth individuals (HNWI) build their investment portfolios. This process required relationship managers to understand the investment goals, risk tolerance and time horizon of their clients before implementing an investment strategy. Robowealth used technology to build user-friendly digital platforms that used algorithms to drive investment decisions. It sought to capitalise on the digitisation trend to reach consumers through an easy-to-download app. Even low-income workers would be able to make small investments and benefit from diversification. Robowealth also developed a business-to-business (B2B) channel that allowed collaborations with other industry players in order to build a more efficient financial ecosystem for locals.